Molecular Analysis of Two Different MRSA Clones ST188 and ST3268 From Primates (Macaca spp.) in a United States Primate Center - Roberts, Marilyn C.; Feßler, Andrea T.; Monecke, Stefan; Ehricht, Ralf; No, David; Schwarz, Stefan (Frontiers in Microbiology, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) were identified in macaques, their environmental facility, and nasal cultures of personnel from the Washington National Primate Research Center [WaNPRC] and included MRSA ST188 SCCmec IV and MRSA ST3268 SCCmec V. The aim of the current study was to determine the carriage of virulence genes, antibiotic resistance genes, and other characteristics of the primate MRSA isolates to determine if there were any obvious differences that would account for differences in transmission within the WaNPRC facility. In total, 1,199 samples from primates were tested for the presence of MRSA resulting in 158 MRSA-positive samples. Fifteen ST188 isolates (all from Macaca nemestrina) and nine ST3268 (four from Macaca mulatta, two from Macaca fascicularis, three from M. nemestrina), were selected for further characterization. All but one of the 15 ST188 isolates had spa type t189 and the remaining one had spa type t3887. These isolates were resistant to β-lactams [blaZ, mecA], macrolides/lincosamides [erm(B)], aminoglycosides [aacA-aphD], and fluoroquinolones. Five isolates were additionally resistant to tetracyclines [tet(K)] and had elevated MICs for benzalkonium chloride [qacC]. In comparison, the nine ST3268 isolates had the related spa types t15469 (n=5) and t13638 (n=4). All nine ST3268 isolates were resistant to β-lactams [blaZ, mecA], and tetracyclines [tet(K)]. Some isolates were additional resistant to aminoglycosides [aacA-aphD], fluoroquinolones and/or showed elevated MICs for benzalkonium chloride [qacC]. The ST3268 isolates had the enterotoxin gene cluster egc [seg, sei, selm, seln, selo, selu] and enterotoxin genes sec and sel and the ST188 isolates did not. The two clones have differences regarding their spa types, virulence and antibiotic resistance genes as well as ST and SCCmec types. However, the data presented does not provide insight into why ST188 spreads easily while ST3268 did not spread within the WaNPRC in-house primates.